Development of a Multimedia-Oriented Problem-Based Learning Model to Support SDG 4: Quality Education for Grade IV Elementary School Students - Endang Saputra; Alwen Bentri; Jasrial; Ulfia Rahmi; Rayendra (Postgraduate, University of Mataram, 2026)
This research is motivated by the low involvement of students in learning Pancasila Education in elementary schools, the limited use of innovative interactive learning media, and the need for a learning model that is able to develop critical, collaborative, and problem-solving skills. This research aims to develop a Canva-based interactive multimedia oriented to the Problem Based Learning (PBL) model that is valid, practical, and effective in improving the learning outcomes of grade IV elementary school students in the subject of Pancasila Education. This type of research is research and development using the ADDIE model which includes five stages, namely analysis, design, development, implementation, and evaluation. The validity of the product is assessed by subject matter experts, media experts, and linguists. Practicality was measured through the responses of teachers and students using questionnaires, while effectiveness was tested through a comparison of pretest and posttest results analyzed using the N-Gain formula. The results of the study showed that the interactive multimedia developed obtained a very valid category with an average score of 89.56%. In addition, this media is stated to be very practical based on positive responses from teachers and students, especially in the aspects of ease of use, attractive visual appearance, and clarity of navigation. In terms of effectiveness, interactive multimedia has been proven to be able to improve students' learning outcomes with an N-Gain value of 77.67 which is included in the high category. Thus, Canva-based interactive multimedia oriented to the PBL model can be an innovative learning media alternative that is valid, practical, and effective to improve the quality of learning.